Weighted risk-free rate and solvency risk assessment of fixed-income security companies for the Ecuadorian stock market - Ojeda, Andrés (2021)
The valuation of stock exchange instruments for the formation of investment portfolios is one of the great financial challenges of recent years. In Ecuador, the stock market is in a period of growth, especially in fixed income securities: these representing more than 95 % of the negotiations carried out in the stock market nationwide in 2019. In this paper, the methodology published by the National Securities Council in 2009 is used for the valuation at prices of market of fixed income securities with the objective of obtaining a discount rate. This is done through calculating the yield curve of sovereign bonds and then applying margins grouping for titles with similar characteristics. The present research work proposes to develop two contributions to this Valuation Operational Manual, given that a little more than a decade has passed since its last development and the current reality us different from that of approxi[1]mately 10 years ago. First, this paper interpolates the internal debt bond curve using the Nelson, Siegel (1987) and Svensson (1994) methodology based on the data of the bond yields for the last quarter of 2019. In addition, in order to obtain a real valuation of the securities traded on the Ecuadorian stock market, a rating system of risk that assesses the stability or solvency of the issuers that trade their securities on the stock market through a binomial logit model is proposed